Reactivation of hypersaline aerobic granular sludge after low-temperature storage - Yao, Chen; Jia Yue, Zhu; Yu, Qin; Zhi Min, Zhang; Shao Chun, Yuan (Tecnología y ciencias del agua, 2017)
Chen, Y., Zhu, J. Y., Qin, Y., Zhang, Z. M., & Yuan, S. C. Â (March-April, 2017). Reactivation of hypersaline aerobic Â granular sludge after low-temperature storage. Â Water Â Technology and Sciences (in Spanish), Â 8 (2), 61-70. Â Â Reactivation of hypersaline aerobic granular sludge after Â low-temperature storage was studied by slowly increasing Â the organic loading. Results indicated that the basic external Â features of thawed hypersaline aerobic granules were still Â largely intact after a six-week low temperature storage, but Â the colors and internal structure changed greatly. Aerobic Â granules experienced a process of particle disintegration, Â fragmentary particles, filamentous bacteria-like particles, Â and dense granules during the recovery process. After Â more than one-month re-cultivation, the settling property, Â dehydrogenase activity, and nitrification properties of Â hypersaline aerobic granules returned to normal. During Â the re-cultivated process, the decentralized growth pattern Â of particles can be effectively controlled, and granules can Â grow compactly by controlling water alkalinity, aeration rate Â and reactor settling time. Â